2021
DOI: 10.1002/joc.7211
|View full text |Cite
|
Sign up to set email alerts
|

The impact of teleconnections on the temporal dynamics in aboveground net primary productivity of the Mongolian Plateau grasslands

Abstract: Temporal dynamics in aboveground net primary productivity (ANPP) are significant for environmental protection and economic development in the Mongolian Plateau grasslands (MPGs). Climate control of ANPP's temporal variations has intensified in response to local meteorological conditions, while the contributions of large-scale atmospheric circulations to ANPP variations are poorly understood in the MPGs. First, we explored the temporal dynamics in annual ANPP, and then, we analyzed correlations among annual ANP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…+IOD brings easterly wind anomalies across the Indian Ocean that diminish rainfall over Australia 46 . Precipitation is enhanced over northern Australia by +PDO in contrast to the eastern and western ends where it is weakened 40 . TSA positively correlated with BA in southeastern Australia probably due to increased surface air temperature during the Austral summer.…”
Section: Oceaniamentioning
confidence: 95%
See 1 more Smart Citation
“…+IOD brings easterly wind anomalies across the Indian Ocean that diminish rainfall over Australia 46 . Precipitation is enhanced over northern Australia by +PDO in contrast to the eastern and western ends where it is weakened 40 . TSA positively correlated with BA in southeastern Australia probably due to increased surface air temperature during the Austral summer.…”
Section: Oceaniamentioning
confidence: 95%
“…AMO, TNA, PNA and EA were the most prominent teleconnections related to wildfire activity in this region. Spring EA is associated with decreased summertime precipitation and reduced aboveground net primary productivity 40 . It has also been observed that a significantly higher sea level pressure and geopotential height in the summer following a warm winter AMO could lead to adiabatic warming and elevated risk of wildfires.…”
Section: Asiamentioning
confidence: 99%
“…Both ENSO and PDO, independently and in combination, influence wet/dry patterns and the prevalence and severity of drought (Hu & Huang, 2009; McCabe et al, 2004). Consequently, recent studies have observed impacts of PDO and ENSO on vegetation biomass and productivity (Bathiany et al, 2018; Chen et al, 2017; Detsch et al, 2016; Jiao et al, 2021). Vegetation in arid dryland regions, such as the southwest United States, is particularly sensitive to climate variation and vegetation state changes (Berdugo et al, 2020; Burrell et al, 2020).…”
Section: Introductionmentioning
confidence: 99%